A Direct Correlation between Viscosity and Liquid Structure in Cu-Sn Alloys. (18th December 2017) - Zhao, Yan; Hou, Xiaoxia
Abstract : The viscosity and liquid structure of C u 100 - x S n x (x = 10, 20, 30, 40, at.%) melts were investigated. Temperature dependence of viscosity η and correlation length D all shows an exponential decay function (Arrhenius-type equation), which is similar to our former studied Cu-Ag alloys. The correlation between viscosity and liquid structure had been studied. A simple relation between viscosity and correlation length D was found. The ratio of D and η shows a linear relationship with temperature, which is different from our former studied results in Cu-Ag alloys. Among the four Cu-Sn alloys, C u 80 S n 20 and C u 70 S n 30 alloys have higher activation energy for viscous flow ( E a, V ), activation energy for structural evolution ( E a, D ), and the slope ( γ ) of the linear relationship of D /η with temperature due to the C u 3 S n clusters formation.